The effect of CPNE7 on periodontal regeneration. (3rd September 2019) - Choung, Han-Wool; Lee, Dong-Seol; Park, Yeoung-Hyun; Lee, Yoon Seon; Bai, Shengfeng; Yoo, Su-Hyang; Lee, Jong-Ho; You, Hyung-Keun; Park, Joo-Cheol
ABSTRACT: Introduction : Preameloblast-conditioned medium (PA-CM), as a mixture of dental epithelium-derived factors, has been reported to regenerate dentin and periodontal tissues in vitro and in vivo . The aim of this study was to investigate the biological effect of Cpne7 on the proliferation, migration, and cementoblast differentiation of periodontal cells in vitro, and on the regeneration of periodontal tissue using periodontal defect model with canine in vivo . Materials and methods : The effect of Cpne7 on cell proliferation, migration, and cementoblast differentiation of periodontal cells were evaluated in vitro . A periodontal defect canine model was designed and the defects were divided into five groups: Group 1: No treatment (negative control), Group 2: Collagen carrier only, Group 3: PA-CM with collagen carrier (positive control), Group 4: PA-CM + CPNE7 Antibody (Ab) with collagen carrier, and Group 5: recombinant CPNE7 (rCPNE7) protein with collagen carrier. Results : Cpne7 was expressed in HERS cells and periodontal ligament (PDL) fibers. By real-time PCR, Cpne7 increased expression of Cap compared to the control. In the periodontal defect canine model, rCPNE7 or PA-CM regenerated periodontal complex, and the arrangement of the newly formed PDL-like fibers were perpendicular to the newly formed cementum and alveolar bone like Sharpey's fibers in natural teeth, while PA-CM + CPNE7 Ab showed irregular arrangement of the newly formed PDL-like fibers compared to the rCPNE7 or PA-CM group. Conclusion : These findings suggest that Cpne7 may have a functional role in periodontal regeneration by supporting periodontal cell attachment to cementum and facilitating physiological arrangement of PDL fibers.